2019
DOI: 10.33245/2310-9289-2019-150-2-131-136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqueous Extract Plant Mixture on Lipid Profile and Hepatotoxicity of Broiler Chicks

Abstract: A research study was conducted to find the effect aqueous extract mixture of Zingiberofficinale, Carumcapticum, Withania somnifera, Trigonella foenum graecum, Silybummarianum, Allium sativum and Berberis lyceum on the growth performance of internal organs, lipid profile and hepatotoxicity of broiler chicks. A total of 240 day old chicks were purchased and were reared for 35 days in summer month. The birds were raised on conventional deep litter system, in open shed and all the pens/cages were placed in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
2
7
0
2
Order By: Relevance
“…Some studies have shown that extracts of various herbs can improve the feed conversion ratio (FCR), decrease the breeding duration, and reduce the breeding cost (Javed et al, 2009). For example, marjoram's effect on tilapia (Oreochromis niloticus) has led to weight gain (WG) and specific growth rate (SGR), as well as to a reduction in FCR and mortality (Hany, et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that extracts of various herbs can improve the feed conversion ratio (FCR), decrease the breeding duration, and reduce the breeding cost (Javed et al, 2009). For example, marjoram's effect on tilapia (Oreochromis niloticus) has led to weight gain (WG) and specific growth rate (SGR), as well as to a reduction in FCR and mortality (Hany, et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mahmood et al (2009) melaporkan pemberian ransum yang mengandung 0,5% bawang putih dapat meningkatkan konversi ransum dan berat badan ayam dan tidak berdampak negatif terhadap perkembangan jantung, rempela, hati, limpa dan pankreas. Javed et al (2009) melaporkan pemberian ekstrak bawang putih 10 ml/liter air minum mengakibatkan konsumsi pakan ,dan kualitas karkas ( persentase karkas, pertambahan berat badan harian dan bobot potong) meningkat serta menurunkan konversi ransum pada ayam broiler umur 35 hari. Ramakrishna et al (2003) mengatakan bahwa suplemen bawang putih (Allium sativum) dapat meningkatkan aktivitas enzim pancreas, sehingga pencernaan bahan pakan lebih baik dan sekaligus dapat meningkatkan penyerapan zat-zat makanan dalam saluran pencernaan.…”
Section: Pendahuluanunclassified
“…Mahmood et al (2009) mengatakan pemberian ransum basal pada ayam broiler yang mengandung tepung bawang putih taraf 0,5% dapat meningkatkan konversi ransum, bobot badan meskipun persentase karkas tidak meningkat. Javed et al (2009) melaporkan bahwa pemberian ekstrak tanaman obat yang mengandung bawang putih 10ml/liter air minum ayam broiler dapat meningkatkan konsumsi ransum, bobot badan, konversi ransum serta kualitas karkas tetapi tidak berpengaruh dengan persentase karkas. Ramakrishna et al (2003) Lemak Abdomen (%) (Fat abdominal) (%) 5,37 ± 0,21 a 5,19 ± 0,90 a 3,87 ± 0,18 a 3,04 ± 0,9 a 3,75 ± 0,13 a Keterangan: P0 = Air minum tanpa penambahan ekstrak metanol bawang putih (kontrol) (drinking water without addition garlic methanol extract 0 ppm (control) ); P1 = Air minum dengan penambahan ekstrak metanol bawang putih 250 ppm (drinking water withaddition garlic methanol extract 250 ppm ); P2 = Air minum dengan penambahan ekstrak metanol bawang putih 500 ppm(drinking water with addition garlic methanol extract 500 ppm); P3 = Air minum dengan penambahan ekstrak metanol bawang putih 750 ppm(drinking water with additiongarlic methanol extract 750 ppm); P4 = Air minum dengan penambahan ekstrak metanol bawang putih 1000 ppm (drinking water with addition garlic methanol extract 1000 ppm)…”
Section: Hasil Dan Pembahasanunclassified
“…In order to increase efficiency by improving digestibility, nutrient absorption and removal of pathogens resident in the gut, Athansiadou et al (2007) announced that phytogenics were introduced into the animal feed diet. Javed et al (2009) suggested that different plant extracts would boost the ratio of feed conversion, increase the quality of carcasses, decrease the broiler's market age and decrease the cost of rearing. Fenugreek (Trigonellafoenum), which has a medicinal plant and a strong spicy and seasoning type of sweet flavour, is one of the various phytogenics available (Blank, 1996).…”
Section: Introductionmentioning
confidence: 99%